Factors affecting the use of Antenatal Care Services in Janiuay, Iloilo a multilevel analysis - Sulatra, Joshua Neal S.; Minerva, Wellken R.; Rezaga, Mark Allan; Esteva, Ysa Key; Juan Loa, Mia Domini
In the 2010 Philippine Health Statistics, Western Visayas had a significantly high MMR of 420 deaths per 100,000 live births. Iloilo is tied with Antique as the provinces with the highest MMR in the region both having 600 deaths in 2013 and 2014, contributing to the high MMR in Iloilo. The use of maternal health services and the factors that affect the individual are important determinants of maternal death. This study aimed to determine the individual and community factors associated with the use of antenatal care services among the mothers of Janiuay, Iloilo. A total of 391 mothers were interviewed form 20 selected barangays using random sampling and proportional allocation. Binary logistic regression was used to calculate for the degree of significance of the individual factors in relation to the utilization of antenatal care. Odds ratio with 95% confidence interval was also calculated to determine the association between individual factors. Breslow-Day test was used to measure homogeneity then Mantel-Haenszel was used to assess the influences of individual, and community level variables on the use of antenatal care services. The significant individual factors found to influence how mothers avail the local antenatal care services were the mother?s age during their delivery in 2013-2014 (p=0.013) and the mother?s marital status during delivery (p=.038) Homogeneous odds ration denote that there is no difference on the impact between the different categories of a given community factor. The results of the study showed that the rural health unit of Janiuay has achieved a good coverage in terms of ANC. Young and unmarried pregnant women usually suffer form inadequate ANC not only because of insufficient information but also due to lack of support of the husband and prejudice form the community. The RHU still needs to put more effort and streamline their projects to target those who are at higher risk for inadequate ANC.